Multifunctional Plumeria rubra nanoparticles: Antimicrobial, antiviral, antiparasitic and anti-inflammatory activities - Bassma H. Elwakil; Mohab H. Elsabrouty; Areej Eskandrani; Keshav Raj Paudel; Esraa Abdelhamid Moneer (Heliyon)
Novel natural nanomaterials are extensively investigated nowadays due to their potential biological activities and low toxicity. In the present investigation, polyvinyl alcohol was used as a green reducing agent to synthesize Plumeria rubra nanoparticles. Plumeria rubra flowers were collected and extracted using a Soxhlet apparatus and examined through gas and liquid chromatography which revealed the presence of palmitic acid, linoleic acid, N-(O-Nitrophenylthio)-l-leucine, plumieridin B, lupeol, and rutin. The antimicrobial activity of the flower extract showed MIC values between 15.6 and 250.0 μg/mL. The optimum conditions for Plumeria rubra nanoparticle synthesis were 30 min stirring time and a 1:1 PVA/Plumeria rubra ratio. The optimized nanoparticles showed antimicrobial activity reached 7.8 μg/mL with entrapment and loading efficiencies %, zeta size, zeta potential, and PDI were 89.0 %, 40.0 %, 18.5 nm, −1.65 mV, and 0.29, respectively. The cytotoxic effect (IC50) of Plumeria rubra nanoparticles reached 503.2 μg/mL. Plumeria rubra nanoparticles showed low antiviral activity against 229E (low-pathogenic coronavirus), with selectivity index 2.90. Moreover, the synthesized Plumeria rubra nanoparticles' anti-inflammatory effect showed effective and selective COX-2 inhibition (IC50 = 4.2 μM, SI = 15.57). On top of that, the synthesized nanoparticles reduced the parasitic tachyzoites’ count by 37, 43, and 49 % in the spleen, brain, and liver, respectively.